Structural Characterization and Isotopic Abundance Ratio Analysis of the Consciousness Energy Healing Treated Ofloxacin - Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Snehasis, Jana (Journal of Current Scientific Research, 2021)
Ofloxacin is an antibiotic, useful against the number of bacterial infections. This scientific investigation was performed to identify the impact of the Trivedi Effect®-Consciousness Energy Healing Treatment on the structural properties and the isotopic abundance ratio of ofloxacin using sophisticated analytical techniques. Ofloxacin sample was divided into control and treated parts. Only the treated ofloxacin received the Consciousness Energy Healing Treatment remotely by a well-known Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. The LC-MS spectra of both the samples of ofloxacin at retention time 3 minutes exhibited the mass of the protonated molecular ion peak at m/z 362.17 (M+H)+. The chromatographic peak area% of the treated ofloxacin (52.4%) was increased by 2.03% compared to the control sample (51.36%). The LC-MS based isotopic abundance ratio of PM+1/PM in the Biofield Treated ofloxacin was significantly increased by 22.43% compared with the control sample. Similarly, the GC-MS based isotopic abundance ratio of PM+1/PM in the Biofield Treated ofloxacin was significantly increased by 19.24% compared with the control sample. The LC-MS and GC-MS based isotopic abundance ratio of PM+1/PM (2H/1H or 15N/14N or 13C/12C or 17O/16O) was significantly increased in the Biofield Treated ofloxacin as compared to the control sample. Thus,2H, 15N, 13C, and17O contributions from (C18H21FN3O4)+ to m/z 363.17 in the treated ofloxacin were significantly increased compared with the control sample. The increased isotopic abundance ratio of the Trivedi Effect®-Consciousness Energy Healing Treated ofloxacin may increase the intra-atomic bond strength and increase its physical stability. The new form of treated ofloxacin would be more stable, better soluble, and bioavailable compared to the control sample. It would be more useful to design efficacious pharmaceutical formulations that might offer better therapeutic response against infections in the urethra, urinary tract, gonorrhoea, pneumonia, infectious diarrhoea, bronchitis, cellulitis, bacterial infection of the eye and ear, multidrug-resistant tuberculosis, prostatitis, otitis media, plague, etc.
Keywords: ofloxacin; The Trivedi Effect®; Biofield Energy; Consciousness Energy Healing Treatment; LC-MS; GC-MS